2022
DOI: 10.1002/slct.202200440
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Substituted Tropones and Advancement for the Construction of Structurally Significant Skeletons

Abstract: Figure 4. Some examples of norditerpene tropones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 201 publications
0
3
0
Order By: Relevance
“…Tropones, a class of non-benzenoid aromatic compounds, have been found in numerous natural products, showing distinct biological activities [1][2][3][4][5]. Aryl-annulated tropone derivatives such as benzotropones [6][7][8][9][10][11][12][13][14][15][16][17] and furotropones [18][19][20][21][22][23] are also attractive molecules because their extended conjugations might exhibit intriguing chemical and photophysical properties (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tropones, a class of non-benzenoid aromatic compounds, have been found in numerous natural products, showing distinct biological activities [1][2][3][4][5]. Aryl-annulated tropone derivatives such as benzotropones [6][7][8][9][10][11][12][13][14][15][16][17] and furotropones [18][19][20][21][22][23] are also attractive molecules because their extended conjugations might exhibit intriguing chemical and photophysical properties (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Pd(OAc)2/PCy3•HBF4 Cs2CO3 (1.2) toluene 110 °C/20 h - 1 Reaction conditions: A mixture of 2aa (0.2 mmol), [Pd] (10 mol%), ligand (20 mol%) and base solvent (2 mL) was heated in an oil bath under N2. 2 NMR yields.…”
mentioning
confidence: 99%
“…For instance, many research projects are carried out to structurally modify vinblastine, tropolones, oridonin, etc. [ 1 , 2 , 3 , 4 , 5 ]. Camptothecin derivatives, another important source for the development of antitumor drugs, exert antitumor activity by inhibiting topoisomerase 1.…”
Section: Introductionmentioning
confidence: 99%
“…The tropone skeleton exists in a number of natural products and bioactive substances, such as colchicine (a monotherapy for acute gout flares and familial Mediterranean fever), harringtonolide (a potent RACK1 inhibitor), and tropodithietic acid (an antibiotic) (Figure ). While tropones are prototypical nonbenzenoid seven-membered aromatic compounds with a carbonyl group, sporadic examples have shown that they can participate in chemical transformations such as cycloaddition, rearrangement, and substitution . Currently, the applications of substituted tropones are significantly limited by their preparative methods.…”
Section: Introductionmentioning
confidence: 99%